The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00701-016-3042-7
|View full text |Cite
|
Sign up to set email alerts
|

eLearning resources to supplement postgraduate neurosurgery training

Abstract: Background: In an increasingly complex and competitive professional environment,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…Our study demonstrated little or no improvement in dermatological knowledge, skills, attitudes and satisfaction among healthcare professionals when compared DHE to traditional learning or no interventions. The results are not specific for dermatology area but are also observed in other medical education setting including nursing, neurosurgery training, palliative care, dental education (14,21,(38)(39)(40)(41). Comparable results show the potential of DHE as a complementary or even alternative intervention to traditional learning.…”
Section: Strength and Limitationsmentioning
confidence: 77%
“…Our study demonstrated little or no improvement in dermatological knowledge, skills, attitudes and satisfaction among healthcare professionals when compared DHE to traditional learning or no interventions. The results are not specific for dermatology area but are also observed in other medical education setting including nursing, neurosurgery training, palliative care, dental education (14,21,(38)(39)(40)(41). Comparable results show the potential of DHE as a complementary or even alternative intervention to traditional learning.…”
Section: Strength and Limitationsmentioning
confidence: 77%
“…The advent of the internet and the ensuing increase in resource accessibility has promoted a shift in the landscape of medical and surgical education. 15,[25][26][27] Learners are increasingly turning to multimedia platforms, and surgical videos in particular, to augment their learning from more traditional modalities (the classroom, the operating room, etc.). One recent survey of fourth-year medical students in Iowa found that 90% of the respondents turn to YouTube the night before a case to review what is expected for the following day.…”
Section: Discussionmentioning
confidence: 99%
“…include digital collections of operative videos, webinars, interactive atlases, and 3D models, now play a central role in the modern era of neurosurgical education for learners all across the globe. 25 Since its internet launch in 2016, The Neurosurgical Atlas by Aaron Cohen-Gadol, MD, has established itself as a leading international resource for neurosurgical education and particularly for microneurosurgical techniques. 24 The site currently features more than 480 text chapters ("volumes"), 9000 illustrations, 1100 educational videos, and 150 "grand-round" webinars presented by renowned neurosurgeons from across the globe.…”
mentioning
confidence: 99%
“…The main projects dealing with the application of digital technology to improve education in the field of neurosurgery in LMICs use e-learning platforms. 4,22 E-learning has been defined as "an approach to teaching and learning, representing all or part of the educational model applied, that is based on the use of electronic media and devices as tools for improving access to training, communication and interaction and that facilitates the adoption of new ways of understanding and developing learning." 4 In 2014, Jotwani et al described the experience of Neurosurgery Education and Training School (NETS), an e-learning platform founded by a multidisciplinary team of specialists as a "free-access, online, multi-authored, multi-institutional database," providing connectivity to neurosurgeons across the world.…”
Section: Current Experiences With Digital Neurosurgical Education Dirmentioning
confidence: 99%
“…Nevertheless, the wide improvement of digital technologies observed in the last decade created a new fascinating array of supportive tools feasible to be integrated into a standard curriculum. 1,11,12,18,22 Some of these new technologies and applications have been designed to support different skills of neurosurgical training, including 3D imagination, procedural automatisms, decision-making, scientific updating and networking. Most of them are freely available online.…”
Section: Neurosurgical Digital Platformsmentioning
confidence: 99%